Fluorescent probes - Gurtler, Volker (Methods in microbiology, 2021)
"Fluorescent Probes, Volume 48 in the Methods in Microbiology series, highlights new advances in the field, with this new volume presenting interesting chapters on important topics, including Hydrogel microarray technology as a tool for clinical diagnostics, The use of probes and bacteriophages for bacteria detection, Probes used with point-of-care microfluidic devices for pathogen detection, Methods for combining FIB/SEM with three-dimensional fluorescence microscopy using CLEM approaches, Probes and Microbes, Microbial signatures associated with cancers, Fluorescent Aptamers for Detection and Treatment of Pathogenic Bacteria and Cancer, Labelled and Unlabeled Probes for Pathogen Detection with Molecular Biology Methods and Biosensors, and much more."--Publisher's web page, viewed May 13, 2021